A case of cutaneous penicilliosis in a child with acute myeloid leukaemia. Issue 5 (23rd September 2015) - Krishnan, Sandhya G.; Sim Tee, Nancy Wen; Tan, Ai Ling; Tan, Ah Moy; Aan Koh, Mark Jean; Chong, Chia Yin; Thoon, Koh Cheng; Hui Tan, Natalie Woon
Abstract : Introduction: We present a case of cutaneous penicilliosis in a paediatric patient with acute myeloid leukaemia (AML). Case report: A 2-year-old boy with AML first developed probable pulmonary aspergillosis during induction chemotherapy in an overseas centre in May 2013, and was treated with AmBisome and voriconazole. When he was admitted to our centre with relapsed AML in October 2013, he was given a fifth course of chemotherapy, and treated with AmBisome for probable pulmonary aspergillosis in view of pulmonary nodular opacities on computed tomography. He thereafter developed an erythematous skin lesion with central eschar on his right hand and left calf. Serum and bronchoalveolar lavage galactomannan antigen (GM Ag) indices increased to a value of >10. AmBisome was changed to voriconazole, and caspofungin was added for 10 days. The left calf skin biopsy showed abundant fungal hyphae with septations. A skin culture grew Penicillium citrinum with MICs (μg ml − 1 ) of: caspofungin 0.016, itraconazole 0.5, amphotericin 1.5 and voriconazole >256.Caspofungin and itraconazole were commenced, and voriconazole was discontinued. The skin lesions and serial GM Ag indices improved. The patient later developed increasing GM Ag indices to a value of >10, which was attributed to Aspergillus flavus left pulmonary mycetoma, which was surgically resected. He eventually succumbed to relapsed AML after a bone-marrow transplant. Conclusion: To the best of our knowledge, this is the first paediatric case of P. citrinum infection. Rising GM Ag indices were attributed to cross-reactivity of Penicillium spp. with GM Ag enzyme immunoassays.